Search for the progress in cancer chemotherapy - Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2003)
All theoretically possible ideas are verified in a search for new anti-cancer drugs. Experience of the several last decades of research have proven that the idea belonging to any category may result in a discovery of the new active compound but simultaneously, none of them guarantees success. The usefulness is finally established using controlled clinical studies and only some of many thousands of substances evaluated reach that stage. This includes the search for new, previously unknown actions of drugs already known and utilized (albeit for different reasons) for years, testing all newly discovered chemical compounds, improving already known anticancer drugs, utilization of the immune system for the generation of anticancer antibodies and search for so called targeted drugs, that is specific inhibitors of proteins playing a role in the neoplastic process i.e. proteins regulating the cellular life and proliferation on various levels. This includes inhibitors of cytokines, cytokine receptors, and signal transduction proteins. The next target the for search of inhibitors is transcription factors. Finally, inhibitors of the mechanisms „cleaning” cells i.e. proteasomes are reaching the clinic stage. Collectively, it should provide many new compounds, and if only some of them would make it to the practice, this will make a significant change. The main goal is to combine effectiveness with low toxicity. The future will tell, whether it is possible to achieve such a target.